Motives for Punishing Powerful Vs. Powerless Offenders: The Mediating Role of Demonization - Fousiani, Kyriaki (Victims & offenders, 2023)
In the present research, we examine how power and group membership of an offender influence observers’ motives for punishment. As compared to powerless offenders, powerful offenders should elicit a stronger motivation of an observer to incapacitate them and protect society (i.e., utilitarian punishment motivation). Moreover, demonization of the offender (e.g., perceiving the offender as evil) should mediate the effect of power on punishing motives. Finally, we investigated whether group membership of an offender would moderate the effects of power on punishing motives. In three studies, we manipulated an offender’s power (high, low) and group membership (ingroup, outgroup, and – in Study 1 – ambiguous). Supporting our hypotheses, all three studies revealed that powerful offenders triggered stronger utilitarian punishment motivation as opposed to powerless offenders, while demonization of the offender mediated this effect. Moreover, Studies 1 and 2 showed that powerless offenders triggered stronger restorative punishment motivation as opposed to powerful offenders while low demonization of the offender mediated this effect. Contrary to our expectations, however, group membership did not moderate the effect of power on observer’s punishing motives. Theoretical and practical implications of these findings are discussed.